AUDIT ENERGI DAN ANALISIS PELUANG PENGHEMATAN ENERGI PADA RUANG KULIAH KAMPUS I IST AKPRIND YOGYAKARTA DALAM UPAYA MENUJU KAMPUS BERWAWASAN LINGKUNGAN - Sukmawati, Paramita Dwi; -, Purnawan (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2021)
Electrical energy is one of the most important human needs and cannot be released from daily needs. Almost all human work requires electrical energy, the use of electrical energy is usually more widely used in large buildings such as office buildings, factories, hotels, and also includes universities that use large-capacity electrical energy. However, the source of energy for electricity generation is conventional energy sources derived from petroleum and coal which if used in excess will be able to endanger and damage the surrounding environment. Steam Power Plant (PLTU), as the largest electricity supplier that has produced electricity through coal burning, contributes to the phenomenon of global warming. In addition, it can also cause depletion of oil and coal reserves due to the non-renewable nature of oil and coal. So, indirectly our consumptive nature of electricity increases the supply of electricity and in the process of producing electricity can damage the environment. Because it has to do with saving electrical energy from households to industries. One method that is often used to make efficient use of electrical energy is the Energy Conservation method. Energy Conservation is an increase in energy efficiency that is used or commonly called the energy saving process, in this method there is an Energy Audit. The energy audit in this study was conducted in the Lecture Room of Campus I IST AKPRIND Yogyakarta in an effort to go to an environmentally friendly campus. The Value of Energy Consumption Intensity (IKE) in the lecture room at Campus I of IST AKPRIND Yogyakarta is very efficient. But for the value of intensity of the lighting in all of the classes do not meet the value of the average lighting levels based on SNI 03-6197-2000, so the lecture room comfort level has not been reached. For this reason, it is necessary to add lighting in the lecture room at Campus I of IST AKPRIND Yogyakarta.